PARTISIPASI MASYARAKAT DESA JAGONG JEGET TERHADAP REHABILITASI HUTAN DI KECAMATAN JAGONG JEGET KABUPATEN ACEH TENGAH MENURUT TEORI ARNSTEIN - Yanto, Indri; Zalmita, Novia (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
This study discusses community participation in forest rehabilitation in Kampung Jagong Jeget, Jagong Jeget District, Central Aceh District based on Arnstein's theory. This study used a qualitative method by distributing research questionnaires. To determine the level of community participation in rehabilitation in Jagong Jeget Village, Jagong Jeget District, Central Aceh District. Data collection was carried out by distributing questionnaires to respondents based on Arnstein's eight participation ladders so that they could be categorized into 3 levels of participation, namely high, medium and low. All parameters given to 38 respondents are in a low position. The highest percentage is in the manipulation stage with a percentage of 14,8 % and the lowest percentage is in the therapy and partnership stages with a percentage of 11,02 %. This means that all parameters of the degree of community participation are still not optimal. Thus it can be concluded that most of the people in Kampung Jagong Jeget, Jagong Jeget District, Central Aceh District are still not participating in forest rehabilitation.